PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XI SMA NEGERI 2 LINTAU BUO - Febriani, Rani (Departemen Matematika, 2024)
An important learning objective for students is to gain an understanding of mathematical concepts. However, class XI at SMA Negeri 2 Lintau Buo still has a low level of competence in this ability. One way to improve it is by applying the STAD (Student Teams Achievement Division) model. This study used a quasi-experimental design, more specifically a posttest only non-equivalent control group design, for its research technique. Students of class XI TP 2024/2025 became the subject of this study. Classes XI.F2 and XI.F1 were randomly selected from the student population to be the research samples. Quizzes and tests were the tools used. The P-value of 0.000, as determined from the test results, is considered statistically significant. As a result, we can say that H0 is not true. Grade XI students who used the STAD model outperformed their peers who relied on direct teaching.Keywords– Understanding Mathematical Concepts, Conventional Learning, Student Teams Achievement Division